(untitled) (CIPEEX, 2025)
Bone health undergoes changes throughout human development and can present significant deficiencies in old age. In this sense, calcium plays a crucial role in the prevention and treatment of osteoporosis, characterized by progressive bone loss, making bones fragile and prone to fractures. This study aimed to analyze the influence of calcium intake on the occurrence of osteoporosis in the elderly. A narrative review was conducted using keywords such as “calcium,” “osteoporosis,” “elderly,” “bone mineral density,” and “supplementation,” crossed with the Boolean operators (AND) and (OR) in the PubMed and Google Scholar databases. Full-text scientific articles in English or Portuguese published between 2020 and 2025 were included. Duplicate files and those that deviated from the topic were excluded. The evidence indicates that adequate calcium intake is directly associated with maintaining bone mineral density and reducing the risk of fractures in the elderly. In Brazil, insufficient calcium consumption is prevalent among the elderly, which is associated with a high incidence of osteoporosis. Calcium supplementation combined with vitamin D and regular physical activity have been shown to be effective in preventing bone loss, helping to preserve bone mass and reduce the risk of fractures. It was concluded that Adequate calcium intake plays a key role in preventing osteoporosis in older adults, and it is essential to implement nutritional and educational strategies aimed at improving the consumption of this mineral in this group, promoting healthy aging and reducing complications related to osteoporosis.